Monte Carlo and Kinetic Monte Carlo Models for Deposition Processes: A Review of Recent Works - Cheimarios, Nikolaos; To, Deifilia; Kokkoris, George; Memos, George; Boudouvis, Andreas G. (Frontiers in Physics, 2021)
Monte Carlo (MC) and kinetic Monte Carlo (kMC) models are widely used for studying the physicochemical surface phenomena encountered in most deposition processes. This spans from physical and chemical vapor deposition to atomic layer and electrochemical deposition. MC and kMC, in comparison to popular molecular methods, such as Molecular Mechanics/Dynamics (MD), have the ability to address much larger time and spatial scales. They also offer a far more detailed approach of the surface processes than continuum-type models, such as the reaction-diffusion models. This work presents a review of the modern applications of MC/kMC models employed in deposition processes.